Infectious diseases - Cohen, J. [ (Jon)] , 1949-; Opal, Steven M.; Powderly, William G. (Mosby, 2010)
Provides comprehensive and practical guidance to help you effectively overcome the advanced clinical infectious disease challenges. This title offers information on various strains of the swine (H1N1) and avian influenza viruses, SARS, nosocomial infections, HIV/AIDS, and many other topics